Pengaruh Diferensiasi Produk Promosi dan Lokasi Terhadap Keputusan Pembelian Batik Lasem Di Kecamatan Lasem Kabupaten Rembang - Riyaningrum, Amilia; Pradhanawati, Ari; Prabawani, Bulan (Jurnal Ilmu Administrasi Bisnis, 2015)
Interviews with batik Lasem owners claim that many outlet their turnover tends to decline, many outlets were closed there is also that they formerly had two or three outlets but now only one outlet that still survive. Some are trying to increase their outlets by developing batik products they sell. Selection of the location of the outlets also they notice and terms of sale are many who try to follow the trends in society that is a way to sell their products in onlineshop. They are aware to follow the trend and understand consumer desires. The purpose of this study was to determine the effect of product differentiation, promotion and location on purchasing decisions batik Lasem in District Lasem of Rembang Regency. This type of research is explanatory research with data collection using questionnaires and literature. This study used a sample of 100 consumers were determined by nonprobability sampling with incidental sampling techniques. Analysis of the data used in this study was to test the validity and reliability, the classical assumption test, multiple linear regression, t-test, f-test and the coefficient of determination. The results showed that; 1) product differentiation has significant positive influence on purchase decisions of batik Lasem (0,000), 2) the promotion has positive and significant impact on purchase decisions of batik Lasem (0.000), 3) location has positive and significant impact on purchase decisions of batik Lasem (0,000), 4) product differentiation, promotion, and location has significant effect on purchase decisions of batik Lasem (0,000). Conclusion This study shows that the more varied batik Lasem products are offered, more interesting and frequent promotions, as well as more affordable and more strategic location of outlets selling batik Lasem the easier access of consumers to reach out and buy the batik Lasem products. Therefore, companies must be able to maintain and improve the quality of product differentiation, enhance the promotion, and choose the location of sales outlets batik Lasem strategically so that consumers are not difficult to find and buy products batik Lasem.